SR AND ND DIFFUSION IN TITANITE - Cherniak D.J. (My University, 1995)
Chemical diffusion of Sr and Nd has been measured in natural titanite under anhydrous conditions. The diffusing species were introduced via powder sources containing Sr or Nd. Concentration profiles were measured by the technique of Rutherford backscattering spectrometry (RBS). Over the temperature range 925-1175°C, the following Arrhenius relations were determined [D in m2 s-1, transport parallel to (100)]:Strontium:log D = -3.57(+/-0.59) + (-415+/-27 kJ mol-1)/2,303RTNeodymium (buffered at QFM):log D = -0.59(+/-1.11) + (-498+/-29 kJ mol-1)/2.303RTSr diffusion appears to be relatively insensitive to fO2 and orientation, while diffusion of Nd in air is approximately an order of magnitude faster than diffusion under QFM conditions.RBS profiles and supplementary measurements of Al using nuclear reaction analysis (NRA) suggest that Sr chemical diffusion involves simple Sr2+ -> Ca2+ exchange. Processes involved in the chemical diffusion of Nd are more complex and appear to depend on the fO2 of the system.Given the slow diffusion rates of both Sr and Nd (and presumably other REE's), closure temperatures are relatively high. Fine-scale zoning in titanite should be preserved under all but the most extreme thermal conditions.